Challenges to MDG Achievement in Low Income Countries : Lessons from Ghana and Honduras - Bussolo, Maurizio (World Bank, Washington, DC, 2012)
This paper summarizes the policy lessons from applications of the Maquette for MDG Simulations (MAMS) model to two low income countries: Ghana and Honduras. Results show that costs of MDGs achievement could reach 10-13 percent of GDP by 2015, although, given the observed low productivity in the provision of social services, significant savings may be realized by improving efficiency. Sources of financing also matter: foreign aid inflows can reduce international competitiveness through real exchange appreciation, while domestic financing can crowd out the private sector and slow poverty reduction. Spending a large share of a fixed budget on growth-enhancing infrastructure may mean sacrificing some human development, even if higher growth is usually associated with lower costs of social services. The pursuit of MDGs increases demand for skills: while this encourages higher educational attainments, in the short term this could lead to increased income inequality and a lower poverty elasticity of growth.